Do Employees Perform Creatively if Provided with Better Facilities from Organizations? Evidence from Pakistan - Fahad Javed Baig; Fasiha Nargis; Muhammad Umair Ashraf; Muhammad Rashid (iRASD Journal of Management)
The employees’ need of appreciation emerges in the form of rewards, empowerment and training, the supply of which fuels up performance of employees gaining indirectly by the organization through the interactive organizational practices grooming their skills which is tested and hypothesized many times. This study contributes by taking into account the inclusion of Creative Performance along with the other tested performance levels and also tests the mediating role of Work Engagement in the established relationships. This study helps in establishing this unique relationship observing the role of mediation also. The effects are analyzed with SPSS (21) and AMOS with Structural Equation modeling. Data is gathered from frontline employees of 06 cities of the Bahawalpur Division in Pakistan. The results show that rewards, empowerment and training foster Work Engagement that in turn elevates levels of Performance of Hotel Industry employees. The findings of this study will rebound to the benefit of the organizations regarding the success factors of their employees at workplace as they can get novelty of service ideas through employees. Its implementation will ultimately result in HR techniques to be adopted to achieve higher levels of performance in future. There are many other High-Performance tools like, Realistic Job Previews, Innovation Programs and Performance based Pay. Future studies can be conducted to assess the impact of these factors also. In addition, some psychological constructs may be included to enhance its area of application and know underlying reasons of divert behaviors. There are many other High-Performance tools like, Realistic Job Previews, Innovation Programs and Performance based Pay. Future studies can be conducted to assess the impact of these factors.